Association between preoperative frailty and postoperative delirium and cognitive dysfunction in elderly patients undergoing surgery under general anaesthesia: A prospective observational study - K Anjaleekrishna; Dalim K. Baidya; Rohit Verma; Bikash R. Ray; Rahul K. Anand; Akhil K. Singh; Souvik Maitra; Puneet Khanna (Indian Journal of Anaesthesia)
Background and Aims: Advancing age is associated with poor physiological reserve to combat stressors of surgery and anaesthesia, which is termed frailty, and it leads to postoperative complications. Frailty has been found to have a strong association with postoperative delirium (POD) and postoperative cognitive dysfunction (POCD) in cardiac surgeries. This study aims to determine the association of frailty with POD and POCD in patients undergoing non-cardiac surgeries. Methods: A prospective observational, cohort study was done at a tertiary-level hospital on 130 patients aged 55 years and above undergoing surgery under general anaesthesia. Preoperative frailty was classified using a 5-factor modified frailty index (5mFI) and sarcopenia [hand grip strength (HGS)]. POD and POCD were assessed with the revised Delirium Rating Scale (DRS) and Addenbrooke’s Cognitive Examination-III at 24 h, 72 h and 30 days after surgery. Association between 5mFI and HGS with postoperative POD and POCD were calculated using linear regression model. Results: Of 117 patients analysed, 58% were identified as frail (5mFI score ≥0.2), exhibiting 2.9 times higher risk of POD [odds ratio (OR) 2.933, 95% confidence interval (CI): 1.001, 8.600, P = 0.050] and 5.8 times higher risk of POCD (OR: 5.380, 95% CI: 1.718, 16.685, P = 0.004) compared to non-frail counterparts. The correlation between 5mFI and postoperative revised DRS-98 scores was statistically significant (P < 0.001), indicating a moderate positive association. However, sarcopenic patients displayed higher but statistically insignificant incidence rates of POD (OR: 1.967, 95% CI: 0.771, 5.014, P = 0.157) and POCD (OR: 1.070, 95% CI: 0.442, 2.589, P = 0.880) than non-sarcopenic patients. Patients with 5mFI scores >0.4 showed a notably increased risk of adverse events within 30 days post-surgery. Conclusions: Our study proves the hypothesis that frailty, apart from age, contributes to POD and POCD. Using 5mFI as a predictor in pre-anaesthetic checkups can help identify vulnerable patients early and implement necessary interventions to decrease the burden of cognitive decline.